Internal Auditor Professionalism: Determinants and Its Effect on Behavior Auditor Ethics - Novien Rialdy; Maya Sari; Syafrida Hani; Jufrizen Jufrizen; Irfan Irfan (Fakultas Ekonomi, Universitas Bangka Belitung, 2023)
This study aims to study the factors that influence the Professionalism and Ethical Behavior of Auditors at BPKP North Sumatra and produce a model of Mediation of Professionalism on the Influence of Moral Intensity and Religiosity on Auditor Ethical Behavior at BPKP North Sumatra. This research is basic (basic research). The strategy employs a quantitative approach. The sample includes all BPKP North Sumatra internal auditors. Using a technique called